2014
DOI: 10.1167/14.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pattern complexity on the visual span for Chinese and alphabet characters

Abstract: The visual span for reading is the number of letters that can be recognized without moving the eyes and is hypothesized to impose a sensory limitation on reading speed. Factors affecting the size of the visual span have been studied using alphabet letters. There may be common constraints applying to recognition of other scripts. The aim of this study was to extend the concept of the visual span to Chinese characters and to examine the effect of the greater complexity of these characters. We measured visual spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(104 citation statements)
references
References 32 publications
9
92
3
Order By: Relevance
“…This finding agrees with a recent report by Wang, He, and Legge (2014) that the visual span in Chinese extends up to 6.7 characters. There are four major differences from the original experiment by Inhoff and Liu (1998).…”
Section: Discussionsupporting
confidence: 94%
“…This finding agrees with a recent report by Wang, He, and Legge (2014) that the visual span in Chinese extends up to 6.7 characters. There are four major differences from the original experiment by Inhoff and Liu (1998).…”
Section: Discussionsupporting
confidence: 94%
“…As mentioned earlier, the accuracy of recognition of the letter that is closest to fixation or the fovea (referred to as the inner letter), is usually much lower than the letter that is furthest from fixation (referred to as the outer letter) 2, 7, 14. The results presented in Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Manipulating the report condition enables an investigation of the effect of memory load on letter recognition accuracy. This study employed the partial and complete report methods 14 . With complete report all 3 or 5 characters were reported (in sequence) whereas in the partial report condition only a single pre-cued letter was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that Pelli et al's finding regarding complexity was partially due to the effect of the size of the word composed by several characters on readability. This possibility is supported by a recent study showing that complexity affects the size of the visual span for characters in text like groups (Wang, He, & Legge, 2014). They found that crowding was the dominant factor limiting the size of the visual span, and the amount of crowding increased with complexity.…”
Section: Legibility and Letter Complexitymentioning
confidence: 67%